Efficacy of Diatomaceous Earth on Ascaridia galli, Blood Parameters: And on Ectoparasites In Chicken - Isabirye, Robert Alex; Waiswa, Charles; Kabi, Fred; Nanyeenya, William N.; Biryomumaisho, Savino; Acai-Okwee, James; Okello, Samuel; Omonuk Akello, Beatrice; Mwesigwa, Moses; Lumu, Richard; Nasinyama, George William (Journal of Agricultural Science and Food Technology, 2019)
The efficacy of diatomaceous earth (DE) in the treatment of chicken against Ascaridia galli and ectoparasites; and its effect on blood parameters in chicken was investigated. Four hundred hens were divided into 5 treatment groups, A, B, C, D and E (n = 80 per group). Groups C, D and E were orally infected with 250 embryonated A. galli eggs while groups A and B were not. Meanwhile, groups A and C fed diets with 2% DE and group D was fed with piperazine; and groups B and E was neither fed with DE nor piperazine. Fecal samples and blood samples were analyzed at week 16 to 22 and; 16 and 36, respectively for fecal egg counts (FEC) and blood parameters (erythrocyte count, hemoglobin content and hematocrit value), respectively. In another experiment, to assess efficacy of DE in treating poultry ectoparasites (fleas, mites and lice) DE was topically applied. Results from biweekly fecal analyses showed significant differences in FEC (P<0.05); and treatment by group (P<0.05) implying that DE had a significant effect in treating A. galli. No significant effects on hematological values were noted (P>0.05). Findings from ectoparasite trials indicated that at certain time points DE eliminated all targeted parasites (efficacy =100%). This study concludes that DE has the potential to control A. galli; and ectoparasites in chicken. Further studies should target effect of DE on internal parasite dynamics for longer periods in chicken. Additionally, to quicken the action of DE against ectoparasites, organic approaches should be studied.
Keywords: Dermanyssus gallinae Echidnophaga spp; Haematological values; Internal parasites; Menopon gallinae and Organic